2015
DOI: 10.4172/2155-6113.1000419
|View full text |Cite
|
Sign up to set email alerts
|

Response to Pneumococcal Polysaccharide Vaccination in Newly Diagnosed HIV-Positive Individuals

Abstract: BackgroundNewly diagnosed HIV-positive individuals are 35 to 100-fold more susceptible to Streptococcus pneumoniae infection compared to non-infected individuals. Therefore, the 23-valent pneumococcal polysaccharide vaccine (PPV23) has previously been recommended, though efficacy and effectiveness of vaccination remains controversial. Early severe B cell dysfunction is a central feature of HIV infection. The specific nature of the immune cells involved in the production of protective antigen-specific antibodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 43 publications
3
39
0
1
Order By: Relevance
“…Loss of memory B cell subsets is associated with impaired antibody responses to pneumococcal vaccination that are incompletely restored by ART [2830]. We have previously shown that both ART-treated and -untreated HIV+ adults exhibit reduced serotype-specific IgM memory B cells after PPV compared to HIV− individuals [26,27]. In addition, a substantial proportion of patients on ART do not achieve normalization of CD4 counts [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss of memory B cell subsets is associated with impaired antibody responses to pneumococcal vaccination that are incompletely restored by ART [2830]. We have previously shown that both ART-treated and -untreated HIV+ adults exhibit reduced serotype-specific IgM memory B cells after PPV compared to HIV− individuals [26,27]. In addition, a substantial proportion of patients on ART do not achieve normalization of CD4 counts [31].…”
Section: Discussionmentioning
confidence: 99%
“…Serotype-specific IgG and IgM serum levels were detected by enzyme-linked immunosorbent assay (ELISA) as previously described using 89SF or 007SP as standards. Opsonophagocytic killing assay (OPA) was performed as previously described [26,27] to determine functional antibody responses. Data were analyzed using the Opsotiter1 software program (University of Alabama at Birmingham).…”
Section: Methodsmentioning
confidence: 99%
“…As the extent of immune recovery at 12 months was greater than at three or six months after cART, the capacity for ongoing reconstitution over time and subsequent effect thereof on immunogenicity and induced-immunological memory of PCV is implied [8]. The late effects of cART could also be inferred from the similar responses found for immunologically AIDS patients immunized immediately compared to those who had received cART for 6 to 12 months before vaccination [62]. The lack of benefit from delaying vaccination and our findings showing that baseline CD4 counts and PVL were not predictive of long-lasting immune responses support the current recommendations of vaccinating all individuals at the time of HIV diagnosis [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies showed no significant improvement in laboratory markers of PPV23 response when immunization is delayed until after ART, and no correlation between viral load, postvaccination immunoglobulin G, and opsonophagocytic titers (OPT) was observed. 18,19 This is in contrast to hepatitis B virus (HBV) vaccine, where responsiveness, as measured by antibody to HBV surface antigen, has been shown to be 2-fold greater with use of ART in HIVinfected patients. 20 Despite high vaccine uptake for the first PPV23 dose, only 50% of eligible patients received the second PPV23 vaccination.…”
Section: Discussionmentioning
confidence: 99%